2014
DOI: 10.1371/journal.pone.0109545
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Methylene Blue by De-Oiled Algal Biomass: Equilibrium, Kinetics and Artificial Neural Network Modelling

Abstract: The main objective of the present study is to effectively utilize the de-oiled algal biomass (DAB) to minimize the waste streams from algal biofuel by using it as an adsorbent. Methylene blue (MB) was used as a sorbate for evaluating the potential of DAB as a biosorbent. The DAB was characterized by SEM, FTIR, pHPZC, particle size, pore volume and pore diameter to understand the biosorption mechanism. The equilibrium studies were carried out by variation in different parameters, i.e., pH (2–9), temperature (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Therefore, the continious experiments were carried out with 4 g/L biosorbent dosage. The results of biosorbent dosage experiment were supported by the results of previous dye biosorption studies reported in the literature (Saeed et al, 2010;Kousha et al, 2012;Maurya et al, 2014;Omar et al, 2018).…”
Section: The Effect Of Biosorbent Dosagesupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, the continious experiments were carried out with 4 g/L biosorbent dosage. The results of biosorbent dosage experiment were supported by the results of previous dye biosorption studies reported in the literature (Saeed et al, 2010;Kousha et al, 2012;Maurya et al, 2014;Omar et al, 2018).…”
Section: The Effect Of Biosorbent Dosagesupporting
confidence: 84%
“…Similarly, in this study maximum percentage of dye biosorption rate occurred with 4 g/L adsorbent dosage as 98.29% (Figure 3). In addition to this, Maurya et al (2014) showed that the percentage of methylene blue dye biosorption rate by algal biomass was increased with the augmentation of biosorbent dosage. Recently, Omar et al (2018) reported that maximum malachite green dye removal rates were increased with the incensement of the amount of 3 algal biomasses called U. reticulata, S. crassifolium and G. corticata.…”
Section: The Effect Of Biosorbent Dosagementioning
confidence: 77%
See 1 more Smart Citation
“…The pH PZC of APNH was found to be 6.92. Generally, adsorption of cations is more favoured at pH > pH PZC while for anions at pH < pH PZC . However, the present study emphasizes the point that electrostatic interactions may not be the only reason for this adsorption process.…”
Section: Resultsmentioning
confidence: 49%
“…The reason is that biosorbent has many signicant advantages such as simple implementation, very low cost, no or minimal use of chemicals and high efficiency, as compared to other materials. Several biosorbents have been used to treat MB and Cr(III) in waste solution such as oak banana peels, 11 sawdust, 27 lawn grass, 28 de-oiled algae, 29 mango leaves, 30 corn cobs, sunower 31 and grapefruit. 32 Pomelo, or Citrus maxima, has been popularly planted in Dong Nai Province, Vietnam.…”
Section: Introductionmentioning
confidence: 99%